2019
DOI: 10.1017/dsi.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Prototype Progress in Digital Fabrication Education

Abstract: The early (pre-requirement) stages of product development can provide relevant insights into the creative design process. At these stages, the communication of ideas during the prototyping process can serve as a rich source for information. In this paper, we attempt to document physical prototypes generated during the design process. We describe the design and preliminary testing of Protobooth Oulu: a system that can be used for documenting the process of prototyping products through capturing process output '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…As such, attempts have been made to aid the process of revision control during a prototyping process through the development of tools for capturing digital representations of each iteration of a prototype. Work in this area has, to date, focussed on capturing 2D images of prototypes to produce a 'snapshot' of each iteration (Barhoush et al, 2019;Erichsen et al, 2020). Whilst 2D representations can certainly provide an indication of a physical artefact's design, their efficacy in communicating the intricacies of each iteration is limited by their inability to capture and convey the detailed geometry of a physical artefact.…”
Section: Introductionmentioning
confidence: 99%
“…As such, attempts have been made to aid the process of revision control during a prototyping process through the development of tools for capturing digital representations of each iteration of a prototype. Work in this area has, to date, focussed on capturing 2D images of prototypes to produce a 'snapshot' of each iteration (Barhoush et al, 2019;Erichsen et al, 2020). Whilst 2D representations can certainly provide an indication of a physical artefact's design, their efficacy in communicating the intricacies of each iteration is limited by their inability to capture and convey the detailed geometry of a physical artefact.…”
Section: Introductionmentioning
confidence: 99%
“…We can compare the number of captures/posts by each team throughout the course. In an earlier study conducted by (Barhoush et al, 2019), it was found that only three of the ten teams actively posted progress using Protobooth. In comparison, the present case study found that eight out of ten teams reported progress in all three stages of prototype development (idea, development, and conclusion) (see Figure 8).…”
Section: Datamentioning
confidence: 98%
“…(iv) The communication module is responsible for communicating information between the on-site system and the repository. Most of the automated systems mentioned in Figure 1 use a Wi-Fi module to communicate information (Barhoush et al, 2019;Sjöman et al, 2017). Other technologies, such as Zigbee and Ethernet, can also be used, depending on the topology and bandwidth required for communication.…”
Section: Future System Anatomymentioning
confidence: 99%
See 2 more Smart Citations